Colonic transit in patients after anterior resection: prospective, comparative study using single-photon emission CT/CT scintigraphy. Issue 5 (10th March 2020) - Ng, K-S; Russo, R; Gladman, M A
Abstract: Background: Bowel dysfunction after anterior resection is well documented, but its pathophysiology remains poorly understood. No study has assessed whether postoperative variation in colonic transit contributes to symptoms. This study measured colonic transit using planar scintigraphy and single-photon emission CT (SPECT)/CT in patients after anterior resection, stratified according to postoperative bowel function. Methods: Symptoms were assessed using the low anterior resection syndrome (LARS) score. Following gallium-67 ingestion, scintigraphy was performed at predefined time points. Nine regions of interest were defined, and geometric centre (GC), percentage isotope retained, GC velocity index and colonic half-clearance time ( T ½ ) determined. Transit parameters were compared between subgroups based on LARS score using receiver operating characteristic (ROC) curve analyses. Results: Fifty patients (37 men; median age 72·6 (range 44·4–87·7) years) underwent planar and SPECT scintigraphy. Overall, 17 patients had major and nine had minor LARS; 24 did not have LARS. There were significant differences in transit profiles between patients with major LARs and those without LARS: GCs were greater (median 5·94 (range 2·35–7·72) versus 4·30 (2·12–6·47) at 32 h; P = 0·015); the percentage retained isotope was lower (median 53·8 (range 6·5–100) versus 89·9 (38·4–100) per cent at 32 h; P = 0·002); GC velocity indices were greater (median 1·70 (range 1·18–1·92) versus 1·45 (0·98–1·80); P = 0·013); and T ½ was shorter (median 38·3 (17·0–65·0) versus 57·0 (32·1–160·0) h; P = 0·003). Percentage tracer retained at 32 h best discriminated major LARS from no LARS (area under curve (AUC) 0·828). Conclusion: Patients with major LARS had accelerated colonic transit compared with those without LARS, which may help explain postoperative bowel dysfunction in this group. The percentage tracer retained at 32 h had the greatest AUC value in discriminating such patients. Graphical Abstract: This study investigated changes in colonic transit after anterior resection, and demonstrated differences in transit profiles between patients with major low anterior resection syndrome (LARS) and those without LARS. This suggests that LARS may be, at least in part, due to changes in postoperative colonic motility, rather than just neorectal or postoperative pelvic floor dysfunction. Increased colonic transit in LARS